Peran Masyarakat dalam PKB bagi Pariwisata yang Berkelanjutan - Amirosa Ria Satiadji (UHN IGB Sugriwa Denpasar, 2018)
Cultural preservation is a very important thing to do so that the existence of a culture in the community will still be hereditary. All parties should contribute to the preservation of the culture. Moreover, Bali is a culture-based tourist destination in its development. So that culture is typical of Bali where tourists visiting Bali really admire it. One of the events best known by Balinese people isthe Bali Arts Festival. The Bali Arts Festival is a cultural event organized by the Provincial Government of Bali with the Bali Provincial Culture Office as the executor. In this study, we want to know whether the role of society in cultural preservation is carried out through an event called the Bali Arts Festival. The research method used is a qualitative method with data collection techniques in the form of interviews and simple quantitative questionnaires distributed to foreign tourists. The results obtained from this study are as follows: The role as an artist, audience, marketer for the Bali Arts Festival event, as parents who support and direct their children, as well as the role of children who love their mothers so that it can take place hereditary.